Enhancing Potato Production using Tuberlet Technology (92-PT-27) in Changing Climatic Circumstances in Bihar - Sinha , Sima; Kumar, Shambhu (Indian Journal of Extension Education, 2018)
The objective of the study was to compare the potato production in two different agro climatic zones of Bihar state by  comparisons between tuberlet (92-PT-27) / true potato seeds, high yielding potato varieties (kufri Ashoka) and farmers'  variety (chandramukhi in Madhepura, sathi in Supaul and jyoti jalandhar in Banka) using true potato seed technology and  evaluating for yield and against major disease, late blight. This trial was conducted on a few selected farmers' field in  Supaul, Madhepura and Banka districts of Bihar state during three consecutive years 2012, 2013 and 2014. Raghopur,  Basantpur and Saraigarh were the blocks selected from Supaul district; Uda Kishanganj, Murliganj and Kumarkhand  from Madhepura district and Banka, Amarpur and Baunsi blocks were selected from Banka district. From every block that  was selected, 10 potato growers were chosen, making a total sample size of 90 potato growers. Selections were done by  random sampling. It was found that average yield of 92-PT-27 was the highest at all three locations as compared to high  yielding varieties and farmers' variety. The benefit cost (BC) ratio was 2.86 for 92-PT-27, which was substantially higher  than 1.87 of Kufri Ashoka and 1.63 of local check. The results reveal that the 92-PT-27 (tuberlet) has a great potential for  commercial production of potato. The TPS technology may serve as a potential alternative to mitigate the problem on non availability of quality seeds.
Keywords: B:C ratio; late blight; solanum tuberosum; True Potato seed; tuberlet